Surgical emergencias due to jejuno-ileal tumors - Sarroca, Carlos; Campos, Néstor; Trostchansky, José; D'Auria, Agustín (Cirugía del Uruguay, 1977)
Retrospective analysis shows that 27 out of 41 jejuno- ileal tumors ( 65. 9 % ) were cases of urgency surgery; 29 of these tumors were malign and 6 benign . Almost ali cases ( 25 out of 27) had previously presented symptomatology over an average peried of 5-6 months. The complication which determined surgery was intestinal occlusion in 48 % of cases; diggestive hemorrhage and peritonitis in 18. 5 % of cases. 62.9 % of patients suffering from malign tumors died as a consequence of this condition. Overall operatory deathrate was 33 o/o.